Fetal adrenal gland size and the ability to predict spontaneous term labor. (September 2019) - Gimovsky, Alexis C.; Pham, Amelie; Shlossman, Philip; Hoffman, Matthew
Abstract: Objective: The objective of this study was to evaluate whether ultrasound measured fetal adrenal gland size can be a predictor of spontaneous term labor. Study design: This study was a diagnostic test accuracy study using a prospective cohort design evaluating the ability of 2-dimensional ultrasound measurement of fetal adrenal gland total length, total width, fetal zone length and fetal zone width in women in the third trimester to predict the primary outcome of spontaneous term labor. Secondary outcomes were vaginal delivery, length of labor, and maternal and neonatal morbidities. Results: Of 43 patients recruited, 3 were excluded. 11 (25.6%) presented in spontaneous labor and 29 (67.4%) underwent induction of labor. Patient demographics were similar for all included except for admission cervical exam and oxytocin use. A receiver operative curve was created to assess test predictability. Weighted width of fetal adrenal gland was the best predictor of spontaneous labor amongst variables measured with an area under the curve of 0.674, p = 0.93. w/W ≥ 0.41 had a sensitivity of 91.0%, specificity of 44.8%, positive predictive value of 38.5% and a negative predictive value of 92.3%. Maternal and neonatal morbidities were not different between the spontaneous labor group and the induction of labor group. Conclusion: Ultrasound measured fetal w/W was moderately predictive of spontaneous labor.